2017
DOI: 10.1108/jfmpc-09-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting tender price in the Ghanaian construction industry

Abstract: Purpose Tender price remains an imperative parameter for clients in deciding whether to invest in a construction project, and it serves as a basis for tender price index (TPI) manipulations. This paper aims to examine the factors affecting tender price in the construction industry. Design/methodology/approach Based on the literature review, nine independent constructs and one dependent construct relating to tender pricing were identified. A structured questionnaire survey was conducted among quantity surveyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…These experts have long-standing experience in the field of quantity surveying and have undertaken several pre-qualification activities. These experts were to ascertain the reasonableness and completeness of the identified variables (Kissi et al , 2017). On this basis, a variable can be deleted or added to the list.…”
Section: Methodsmentioning
confidence: 99%
“…These experts have long-standing experience in the field of quantity surveying and have undertaken several pre-qualification activities. These experts were to ascertain the reasonableness and completeness of the identified variables (Kissi et al , 2017). On this basis, a variable can be deleted or added to the list.…”
Section: Methodsmentioning
confidence: 99%
“…Their results showed that price increase including material cost escalation is one of the ten major cost overrun factors. Kissi et al (2017) examined the factors that affect price estimation in the tender stage of construction projects using least square-structural model (PLS-SEM). Barraza and Bueno (2007) offered a simple heuristic approach to manage cost contingencies in construction projects using Monte Carlo simulation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The trend lines, which are used the most during the design of the extrapolation forecasts (prognosis), contain two or three parameters. Based on the significance of the estimation of the parameters of the trend line, a second-degree polynomial has been chosen [11].…”
Section: The Methods Of the Price Development Forecast Based On The Anmentioning
confidence: 99%
“…In conclusion, the authors highlight the need for consultation and expert discussion using any statistical method used to predict an offer in the construction sector. In the construction practice, those statistical methods may also have a practical use, especially during the design of the tender price from the contractor's point of view, in his company's pricing policy [11].…”
Section: Literature Researchmentioning
confidence: 99%